Typicality and trajectories of problematic and positive behaviors over adolescence in eight countries - Buchanan, Christy M.; Zietz, Susannah; Lansford, Jennifer E.; Skinner, Ann T.; Di Giunta, Laura; Dodge, Kenneth A.; Gurdal, Sevtap; Liu, Qin; Long, Qian; Oburu, Paul; Pastorelli, Concetta; Sorbring, Emma; et al. (Frontiers in Psychology, 2023)
In this study, we examine the predictions of a storm and stress characterization of adolescence concerning typicality and trajectories of internalizing, externalizing, and wellbeing from late childhood through late adolescence. Using data from the Parenting Across Cultures study, levels and trajectories of these characteristics were analyzed for 1,211 adolescents from 11 cultural groups across eight countries. Data were longitudinal, collected at seven timepoints from 8 - 17 years of age. Thus, the data provide insight into developmental change as well as typicality of behaviors across several countries. We found more support for a storm and stress characterization with respect to the developmental trajectories of behavior and characteristics from childhood to adolescence or across the adolescent years than with respect to typicality of behavior. Overall, adolescents’ behavior was more positive than negative in all cultural groups across childhood and adolescence. There was cultural variability in both prevalence and trajectories of behavior. We argue that a more positive and nuanced characterization of adolescence is appropriate and important.